Dyadic psychological intervention for patients with cancer and caregivers in home-based specialized palliative care: The Domus model. Issue 2 (30th March 2017) - von Heymann-Horan, Annika B.; Puggaard, Louise B.; Nissen, Kathrine G.; Benthien, Kirstine Skov; Bidstrup, Pernille; Coyne, James; Johansen, Christoffer; Kjellberg, Jakob; Nordly, Mie; Sjøgren, Per; Timm, Helle; von der Maase, Hans; et al.
ABSTRACT: Objective: Patients with incurable cancer and their informal caregivers have numerous psychological and psychosocial needs. Many of these patients wish to receive their care and die at home. Few home-based specialized palliative care (SPC) interventions systematically integrate psychological support. We present a psychological intervention for patient–caregiver dyads developed for an ongoing randomized controlled trial (RCT) of home-based SPC, known as Domus, as well as the results of an assessment of its acceptability and feasibility. Method: The Domus model of SPC for patients with incurable cancer and their caregivers offered systematic psychological assessment and dyadic intervention as part of interdisciplinary care. Through accelerated transition to SPC, the aim of the model was to enhance patients' chances of receiving care and dying at home. Integration of psychological support sought to facilitate this goal by alleviating distress in patients and caregivers. Psychologists provided needs-based sessions based on existential-phenomenological therapy. Feasibility and acceptability were investigated by examining enrollment, nonparticipation, and completion of psychological sessions. Results: Enrollment in the RCT and uptake of the psychological intervention indicated that it was feasible and acceptable to patients and caregivers. The strengths of the intervention included its focus on dyads, psychological distress, and existential concerns, as well as interdisciplinary collaboration and psychological interventions offered according to need. Its main limitation was a lack of an intervention for other family members. Significance of Results: Our results show that psychological intervention can be systematically integrated into SPC and that it appears feasible to provide dyadic needs-based sessions with an existential therapeutic approach. The Domus RCT will provide evidence of the efficacy of a novel model of multidisciplinary SPC.